KOMUNIKASI DAN DISPOSISI DALAM IMPLEMENTASI PROGRAMPENYELENGGARAAN PERKEBUNANKELAPA SAWIT - E.01108042, Alias (FISIP Universitas Tanjungpura, 2013)
The pros and cons in the community during the entry of PT. Megasawindo Mighty Long Buluk Hamlet impact on the emergence of problems in society, such as the threat of eviction from their homes by the local community to community pro cons of the palm, with the company's agreement not to use stamp. This study aims to identify and understand communication sertadisposisi (attitude) companies to government policy during the process of acquisition of land, in the manner of payment of compensation of land and crops and buildings thereon or other items owned by holders of land rights, the garden development plan given by the company to the public, in the process of cultivating the land for oil palm plantations. The study was conducted with the pre-survey the field first in order to know the situation and condition of the location will be the research and after getting the facts and supporting information, then the researchers took into account whether the location will be the target of the research has some problems phenomenon worthy of study. As the obtained data the researchers collected multiple informants in the study subjects interviewed them, make observations, and documentation. After some data about the material under study is obtained, the researchers conducted a review of the crosscheck and the data, and compare each of the data obtained in order to get appropriate answers to the problem under study.The study found that communication and disposition of oil palm plantation company PT. Perkasa Megasawindo policies made by the government during the administration of oil palm plantations in progress, has not gone well, because there are many irregularities that occurred. Weak communication and disposition of the company that became one of the causes of violation of public policy that has been made by the government. Companies need to communicate better to the government and the people, in order to facilitate the development of the company. Unfavorable attitude of the implementor needs to be changed, for the achievement of better policies and for the realization of hopes and ideals together.Â Keywords: Communication policies, disposition implementor, the implementation of palm oil plantations.Â Â